A comprehensive and mechanistic review on protective effects of kaempferol against natural and chemical toxins: Role of NF‐κB inhibition and Nrf2 activation. (5th December 2022) - Hosseini, Azar; Alipour, Alieh; Baradaran Rahimi, Vafa; Askari, Vahid Reza
Abstract: Different toxins, including chemicals and natural, can be entered from various routes and influence human health. Herbal medicines and their active components can attenuate the toxicity of agents via multiple mechanisms. For example, kaempferol, as a flavonoid, can be found in fruits and vegetables, and has an essential role in improving disorders such as cardiovascular disorders, neurological diseases, cancer, pain, and inflammation situations. The beneficial effects of kaempferol may be related to the inhibition of oxidative stress, attenuation of inflammatory factors such as tumor necrosis factor‐alpha (TNF‐α), interleukin‐6 (IL‐6), cyclooxygenase‐2 (COX‐2) and nuclear factor ĸB (NF‐ĸB) as well as the modulation of apoptosis and mitogen‐activated protein kinase (MAPK) signaling pathways. This flavonoid boasts a wide spectrum of toxin targeting effects in tissue fibrosis, inflammation, and oxidative stress thus shows promising protective effects against natural and chemical toxin induced hepatotoxicity, nephrotoxicity, cardiotoxicity, neurotoxicity, lung, and intestinal in the in vitro and in vivo setting. The most remarkable aspect of kaempferol is that it does not focus its efforts on just one organ or one molecular pathway. Although its significance as a treatment option remains questionable and requires more clinical studies, it seems to be a low‐risk therapeutic option. It is crucial to emphasize that kaempferol's poor bioavailability is a significant barrier to its use as a therapeutic option. Nanotechnology can be a promising way to overcome this challenge, reviving optimism in using kaempferol as a viable treatment agent against toxin‐induced disorders.